Assessing the Long Case in Undergraduate Medical Students: Development of Structured, Feasible, Valid and Reliable Tool - Rehan Ahmed Khan, Fahd Mudassar Hameed, Masood Anwar (Journal of Islamic International Medical College, 2014)
Objective: To develop structured, feasible, valid and reliable tool in assessing long case in undergraduate medical student. Study Design: Qualitative Action Research. Place and Duration: IIMCT, Aug, 2012 to Oct 2013. Materials and Methods: An action research approach was used. Problems of un-structured examination in long case were identified. Delphi technique with the senior faculty was used to identify the components of the assessment tool. Final draft of the tool was sent to medical educationists for their input. Results: A structured tool (SLICE) for examining the holistic approach of student towards managing a patient was developed and was found to be reliable (Cronbach alpha 0.87) and valid. Conclusion: SLICE is a feasible, valid and reliable tool to assess long case in undergraduate medical students in our setup.